CONSUMER PROTECTION AS AN INSTRUMENT FOR FULFILLING HUMAN RIGHTS IN THE ECONOMIC SECTOR AND ITS CONSTITUTIONALIZING EFFORTS IN THE 1945 CONSTITUTION - Musa Taklima; Adi Sulistiyono; M. Syamsudin (Fakultas Syariah, 2023)
Humans are ipso facto consumers who are entitled to their rights that must be protected under contract and law. Consumers, as human beings, have human rights that must be protected, respected, fulfilled, and promoted by the state. There is a vital intersection between consumer rights and human rights. The right to a decent standard of living is a human right to food, clothing, and housing. Fulfillment of human rights can be pursued by adequate protection of consumer rights. The effectiveness of protecting consumer rights can be realized by rooting them in the constitution to allow them to become fundamental rights and empower public authorities in fulfilling, respecting, implementing, and enforcing them so that the goal of consumer protection is achieved in maintaining human dignity and status where this is a value of humanization, liberation, and transcendence from the perspective of prophetic law. The research is expected to offer a recommendation for the government and the People’s Consultative Assembly (MPR) amidst the urgency of constitutionalizing consumer rights in the Constitution to support the recognition of consumer rights as universal human rights.Manusia, warganegara ipso facto konsumen. Manusia sebagai konsumen memiliki hak-hak yang harus dilindungi tidak hanya oleh kontrak akan tetapi hukum. Konsumen sebagai manusia memiliki hak asasi yang harus dilindungi, dihormati, dipenuhi dan dimajukan oleh negara. Terdapat keteririsan yang kuat antara hak-hak konsumen dengan hak asasi manusia. Hak atas standar hidup yang layak merupakan hak asasi manusia di bidang yang mencakup pangan, sandang dan perumahan. Pemenuhan HAM ini dapat diusahakan dengan perlindungan hak-hak konsumen yang efektif. Efektivitas perlindungan hak-hak konsumen dapat diwujudkan dengan mengakarkannya dalam konstitusi sehingga menjadi hak fundamental dan dapat memberdayakan otoritas publik dalam pemenuhan, penghormatan, pelaksanaan dan penegakannya, sehingga tujuan perlindungan konsumen tercapai dalam menjaga harkat dan martabat manusia di mana hal tersebut merupakan nilai humanisasi, liberasi dan transendensi dalam perspektif ilmu hukum profetik. Penelitian diharapkan menjadi rekomendasi bagai pemerintah dan Majelis Permusyawaratan Rakyat (MPR) terkait urgensi konstitusionalisasi perlindungan hak-hak konsumen dalam UUD sebagai upaya mendukung pengakuan hak-hak konsumen sebagai hak asasi manusia yang bersifat universal.